Manajemen Pengelolaan Pos Kesehatan Pesantren untuk Mewujudkan Pesantren Sehat - Inayati, Isna Nurul; Al Karim , Muhammad Busro; Fitri , Rahma Dika Kartika; Wahyuni, Pingki Tri; Wijaya , Nova Dwi Rahma; Agita , Salsa Zaina Isabella; Prastyo, Angga Teguh; Ulfa, Nanik; Nurwakhidah, Ana (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2025)
The availability of Poskestren (Islamic Boarding School Health Post) is crucial in fostering a clean and healthy lifestyle among students. However, many students lack the competence to manage Poskestren effectively. To address this, an educational initiative was conducted at PP Assalam Jambewangi using the Participatory Action Research (PAR) method. This approach involved collaborative efforts between the service team, the boarding school, and the local health center. The activities included initial condition analysis, focus group discussions, education on Poskestren management, and reflection sessions. The results showed a significant increase in students' knowledge and participation, along with their enthusiasm to revitalize Poskestren. The smooth implementation of this program highlights the positive impact of management education in supporting a healthy Islamic boarding school environment.